2018
DOI: 10.3389/fpsyg.2018.01975
|View full text |Cite
|
Sign up to set email alerts
|

Contingent National Belonging: The Perceived Fit and Acceptance of Culturally Different Peers Predicts Minority Adolescents' Own Belonging

Abstract: Prevailing definitions of national identities in Europe equate belonging to the nation with “fitting in” culturally and leave immigrant minorities who are culturally different from the majority group struggling to belong. The present study focuses on an under-researched minority perspective on the intersubjective cultural contents of the national identity. We propose that minorities' national belonging is contingent on their perception that minority peers who deviate from the majority culture are accepted as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 64 publications
(96 reference statements)
1
23
0
1
Order By: Relevance
“…In more homogeneous contexts, dominated by a large majority of non-immigrant students, ethnic minority adolescents may face higher pressures for assimilation. The examined schools, by contrast, were ethnically heterogeneous and thus youth may have felt less pressured to assimilate—in line with the balance of power principle (Juvonen et al 2006 ) and previous research on the role of school ethnic composition for minority youth’ sense of national belonging (Gharaei et al 2018 ).…”
Section: Discussionmentioning
confidence: 56%
“…In more homogeneous contexts, dominated by a large majority of non-immigrant students, ethnic minority adolescents may face higher pressures for assimilation. The examined schools, by contrast, were ethnically heterogeneous and thus youth may have felt less pressured to assimilate—in line with the balance of power principle (Juvonen et al 2006 ) and previous research on the role of school ethnic composition for minority youth’ sense of national belonging (Gharaei et al 2018 ).…”
Section: Discussionmentioning
confidence: 56%
“…National disidentification is also not, according to the authors, correlated with ethnic identification: it is a response to experiences of discrimination in its own right (Jasinskaja-Lahti et al, 2009). In line with this work, research since has found that Muslim youth who felt that their religious identities did not fit, or were culturally unacceptable, reported decreased national identification (Gharaei et al, 2018). Moreover, positive intergroup contact has been shown to increase national identification among Muslims across Europe (Fleischmann & Phalet, 2017).…”
Section: Sense Of Belonging Social Integration and The Effects Of Discriminationmentioning
confidence: 79%
“…In more homogeneous contexts, dominated by a large majority of non-immigrant students, ethnic minority adolescents may face higher pressures for assimilation. The examined schools, by contrast, were ethnically heterogeneous and thus youth may have felt less pressured to assimilatein line with the balance of power principle (Juvonen, Nishina, & Graham, 2006) and previous research on the role of school ethnic composition for minority youth' sense of national belonging (Gharaei, Phalet, & Fleischmann, 2018).…”
Section: Distribution and Meaning Of Acculturation Profiles Of Identimentioning
confidence: 89%